Laser speckle velocimetry for robot manufacturing - Charrett, Thomas O. H.; Bandari, Yashwanth K.; Michel, Florent; Ding, Jialuo; Williams, Stewart W.; Tatum, Ralph P. (SPIE, 2017)
A non-contact speckle correlation sensor for the measurement of robotic tool speed is presented for use in robotic manufacturing and is capable of measuring the in-plane relative velocities between a robot end-effector and the workpiece or other surface. The sensor performance was assessed in the laboratory with the sensor accuracies found to be better than 0:01 mm/s over a 70 mm/s velocity range. Finally an example of the sensors application to robotic manufacturing is presented where the sensor was applied to tool speed measurement for path planning in the wire and arc additive manufacturing process using a KUKA KR150 L110/2 industrial robot.
Keywords: Laser speckle; tool speed sensor; velocimetry; robotic sensor